A discourse analysis of interviews in sport in english and vietnamese - Lê,Thị Tâm (ĐHĐN., 2015)
This study aims at conducting a discourse analysis of interviews in sports in English and Vietnamese in order to discover some typical discourse features and then find out the similarities and differences in terms of the layout, lexical features, syntactic features and cohesive devices between these two kinds of sport interviews. The study is carried out based on the theories of discourse analysis and a combination of a variety of methods such as qualitative, quantitative, descriptive and contrastive analysis. 100 samples of sport interviews in English and 100 samples of sport interviews in Vietnamese were collected from the internet for recent years. The findings showed that along with some similarities, there were a number of noticeable differences. In terms of the layout, EIS and VIS share a similar layout which consists of headline, introduction, body and conclusion. In terms of lexical features, EIS uses the attributive adjectives commonly while VIS prefers to use the borrowing words frequently. With regard to the syntactic features, reported speech and common structures are investigated respectively. Finally, cohesive devices reveals reference, repetition and conjunction are the prominent devices used in both English and Vietnamese sport interviews. Based on the findings, the thesis presented some implications and suggestions for learning and teaching in English. It is hoped that the results of the thesis are useful for those who are interested in sport interviews